Reappraisal of Immotthia in Dictyosporiaceae, Pleosporales: Introducing Immotthia bambusae sp. nov. and Pseudocyclothyriella clematidis comb. et gen. nov. Based on Morphology and Phylogeny - Jiang, Hong-Bo; Jeewon, Rajesh; Karunarathna, Samantha C.; Phukhamsakda, Chayanard; Doilom, Mingkwan; Kakumyan, Pattana; Suwannarach, Nakarin; Phookamsak, Rungtiwa; Lumyong, Saisamorn (Frontiers in Microbiology, 2021)
Immotthia is a poorly known genus, and currently, no DNA sequence data are available to ascertain its proper phylogenetic placement and evolutionary relationships with other bitunicate fungi. To date, there are only two species accepted in the genus. During our ongoing research study of bambusicolous fungi in southwest China and Thailand, a fungus associated with stromata of Hypoxylon sp. was found on dead bamboo culms in Loei Province, Thailand. Preliminary morphological identification revealed that the fungal collection belongs to Immotthia. A novel species, Immotthia bambusae, is introduced herein based on a comparison of morphological characteristics with the type specimen of I. hypoxylon (≡ Amphisphaeria hypoxylon Ellis and Everh.), a synonym of I. atrograna (Cooke and Ellis) M. E. Barr. Phylogenetic analyses of a concatenated ITS, LSU, SSU, and TEF1-α DNA sequence matrix showed that Immotthia belongs to Dictyosporiaceae, Pleosporales. Despite I. bambusae strains constituting a supported subclade, they are nested with the genus Pseudocoleophoma. Pseudocoleophoma clematidis is morphologically different from all other Pseudocoleophoma species, while its conidial characteristics are similar to Cyclothyriella. Multigene phylogenetic analyses showed that P. clematidis formed a clade basal to Immotthia, separated from Pseudocoleophoma with strong statistical support. Therefore, we introduce a monotypic genus, Pseudocyclothyriella Phukhams. and Phookamsak, gen. nov. to accommodate the single species, Pseudocyclothyriella clematidis (Phukhams. and K. D. Hyde) Phukhams. and Phookamsak, comb. nov. Detailed descriptions, color micrographs, and phylogenetic trees to show the placement of the new taxa are provided. In addition, an updated taxonomic treatment of the genera Immotthia and Pseudocyclothyriella is also provided based on the study of the type materials and phylogeny generated from DNA sequence data.